2022
DOI: 10.1109/access.2022.3146424
|View full text |Cite
|
Sign up to set email alerts
|

Single-Point Crossover and Jellyfish Optimization for Handling Imbalanced Data Classification Problem

Abstract: The imbalanced datasets and their classification has pulled in as a hot research topic over the years. It is used in different fields, for example, security, finance, health, and many others. The imbalanced datasets are balanced by applying resampling and various solutions are designed to tackle such datasets that mainly focus on class distribution issues. The imbalanced data is rebalanced using these methods. This paper introduces a technique for balancing data through two stages: first, oversampling methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
(19 reference statements)
0
6
0
1
Order By: Relevance
“…This AJS is one of the newly proposed meta-heuristic swarm-based optimization algorithms derived by simulating the locomotion and dietary patterns [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] of jellyfish. Jellyfish are the most efficient swimmers of all aquatic animals widely seen in the oceans having umbrella-shaped bells and trailing tentacles.…”
Section: Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This AJS is one of the newly proposed meta-heuristic swarm-based optimization algorithms derived by simulating the locomotion and dietary patterns [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] of jellyfish. Jellyfish are the most efficient swimmers of all aquatic animals widely seen in the oceans having umbrella-shaped bells and trailing tentacles.…”
Section: Methodologiesmentioning
confidence: 99%
“…The key advantages of the ensemble learning mechanism to design a robust feature selection model by proposing combined feature fusion strategies [ 19 , 20 , 21 ], such as combined feature set (CFS), adaptive weighted feature set (AWFS), model-based optimized weighted feature set (MOWFS), and feature-based optimized weighted feature set (FOWFS), are experimented and validated. In order to reduce the losses and selection of optimized weights of those three pre-trained networks, the advantages of a new meta-heuristic optimizer artificial jellyfish optimizer (AJS) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] was used and finally, the performance of the proposed feature fusion strategies are likened to other combinations of the models with genetic algorithm (GA) [ 30 ] and particle swarm optimization (PSO) [ 31 ] such as MOWFA-GA, MOWFS-PSO, FOWFS-GA, and FOWPS-PSO, and it was observed that the proposed combination of FOWFS-AJS outperforms the other models used for classification of skin lesion diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Teknik optimasi pada dataset tidak seimbang telah banyak dikembangkan [11]. Beberapa teknik optimasi diantaranya adalah dengan pendekatan level data [12], pendekatan pada level algoritma dan pendekatan pada keduanya [13]. Dengan pendekatan level data, beberapa teknik digunakan dalam proses optimasi, diantaranya adalah melakukan oversampling pada data [14].…”
Section: Pendahuluanunclassified
“…They applied the proposed algorithm to ten datasets and compared it with competing algorithms using various metrics; the hybrid algorithm outperformed. Desuky et al 92 used JSO to classify imbalanced and balanced datasets. They performed experiments on 18 real imbalanced datasets, and the proposed method performed comparably with well-known and recently developed techniques.…”
Section: Applicationsmentioning
confidence: 99%
“…Optimizing CNN hyper-parameters JSO Chou et al 90 Predicting peak friction angle of fiber-reinforced soil (FRS) JSO-WFLSSVR Chou et al 93 Classification of concrete as shallow or deep spalling JSO Hoang et al 94 Clustering renewable energy based microgrid JSO Shubham et al 99 Predicting optimal switching angle in voltage control JSO Siddiqui et al 95 Predicting performance of STEACS RVFL-JSO Almodfer et al 89 Benchmark function optimization and data clustering LA-JSO Barshandeh et al 91 Classifying imbalanced and balanced datasets JSO Desuky et al 92 Integrated interval forecasting for solar radiation MOJS Wang and Gao 97 Classifying human brain functions JSO Zhao 98 Forecasting income of rural residents FOGJSO Lei et al 61…”
Section: Prediction and Classificationmentioning
confidence: 99%